2009
DOI: 10.1002/ejoc.200900148
|View full text |Cite
|
Sign up to set email alerts
|

The Observation of the C–H···O Hydrogen Bond in Trisialic Acid Lactone and Its Implications for Cooperative Lactonization

Abstract: The C–H···O sp 3 hydrogen bond in trisialic acid lactones has been examined by using long‐range COSY (LRCOSY) and ab initio calculations. From an analysis of the LRCOSY spectra, 3J correlations of BH9ax/AH8 and CH9ax/BH8 confirmed the existence of hydrogen‐bond connections of x+1C9–x+1H9ax···xO8. The theoretical bond energy of the hydrogen bond was estimated to be 1.0 or 1.6 kcal/mol by using two models. The acid‐catalyzed cooperative lactonization of oligosialic acids can be understood in terms of the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Nonconventional Hbonds in glycans have been observed in DMSO. 4 In this report, we provide direct NMR evidence for this Hbond in the sialyl Lewis-X pentasaccharide (sLe X -5) 5 in H 2 O (Figure 1A). Moreover, we performed an extensive temperature-dependent NMR structural study in conjunction with molecular dynamics (MD) simulations to provide novel evidence for two conventional Hbonds in rapid equilibrium.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Nonconventional Hbonds in glycans have been observed in DMSO. 4 In this report, we provide direct NMR evidence for this Hbond in the sialyl Lewis-X pentasaccharide (sLe X -5) 5 in H 2 O (Figure 1A). Moreover, we performed an extensive temperature-dependent NMR structural study in conjunction with molecular dynamics (MD) simulations to provide novel evidence for two conventional Hbonds in rapid equilibrium.…”
mentioning
confidence: 64%
“…With the Le X core structure well described, it is possible to analyze the available pathways for magnetization transfer (Figure 3B, red and blue dots) leading to the observed NMR signals. The three signals observed can be interpreted equally well as resulting from 4 J CH or 2 J CH with either Gal{IV}O5 or GlcNAc{II}O4 as acceptor. The average distances between Fuc{III}H5 and its nearest oxygen neighbors, in the NMR derived structure at 37 °C, are Gal{IV}O5 (2.4 ± 0.2) and GlcNAc{II}O4 (2.3 ± 0.2).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Also, we compared the 1 H NMR spectra of the lactonized trimer 4 prepared by electrolysis at pH 4.2 and the lactonized product formed by acid catalysis in acetic acid (Figure ). The spectra were identical, which indicated that the lactonization of trimer 1 can occur by either acidic catalysis or applying an electric current. Besides, the lactonized product 4 was not formed with an electrical current of 100 μA in a neutral buffer solution (Figure d) and pH 5 (Figure S7).…”
Section: Introductionmentioning
confidence: 87%
“…Samples were prepared from (a) acid‐catalyzed lactonization in acetic acid and (b) electrochemical lactonization with a constant current of 100 μA for 20 min in 0.2 M NaClO 4 /100 mM PBS, pH 4.2. For chemical shift assignment, refer to previous publications…”
Section: Introductionmentioning
confidence: 99%